The effects of organophosphate exposure on non target terrestrial and aquatic organisms following different exposure regimes : linking biomarker responses and life-cycle effects - Jordaan, Martine Saskia (2010)
Thesis (PhD (Botany and Zoology))--University of Stellenbosch, 2010.